THE EARLY CAMBRIAN HELCIONELLOID MOLLUSC ANABARELLA VOSTOKOVA - Gubanov A.P.; Peel J.S. (My University, 2003)
One of the oldest known helcionelloid molluscs, Anabarella Vostokova, is redescribed on the basis of type material from the lower Cambrian of north Siberia. Published records of the type species, Anabarella plana Vostokova, show a very wide range in morphology, but studies of variation through ontogeny and in taphonomy confirm assignment to a single variable species. Other described species are reviewed.
Keywords: Lower Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская